EFEKTIVITAS MEDIA AUDIOVISUAL KOSWA (KOSAKATA JAWA) DALAM MENINGKATKAN KEMAMPUAN MEMBACA KOSAKATA BAHASA JAWA KELAS II SD NEGERI 1 GUYANGAN - Amran Dzaki Mubarok, Muhammad; Dwiana Asih Wiranti; Abdullah Efendi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to measure the effectiveness of KOSWA (Javanese Vocabulary) audiovisual media in improving the ability to read Javanese vocabulary in grade II students of SD Negeri 1 Guyangan. The background of this study is based on the need for contextual, interactive learning media that support the preservation of regional languages. The method used is a quantitative experiment with One Group Pre-test Post-test Design. The research sample was selected using saturated sampling techniques with 21 students. Data were analysed through descriptive statistics and paired sample t-test using the SPSS version 25 application. The analysis results showed an increase in the average value from 43.81 (pre-test) to 78.10 (post-test). The t count value of 16.54> t table -16.946 and a significance value of 0.000 <0.05. These findings indicate that KOSWA media is effective in improving students' ability to read Javanese vocabulary. In addition, this media also encourages critical thinking skills, collaboration, and fosters motivation and positive character in students. This finding is reinforced by the principles of multimedia learning and various previous studies that highlight the importance of digital media in language learning and preserving local culture. Thus, KOSWA becomes a strategic learning medium to support interactive, contextual Javanese language education, preserving local cultural languages ​​and sustainability.